Ice needle dry particle, ceramic tile with ice needle effect and preparation method of ceramic tile

By using specially designed ice needle dry particles and inkjet printing technology on ceramic tiles, combined with matte covering glaze, the problem of the lack of innovation and artistry of traditional ceramic tiles is solved, and the high-quality, good-looking glaze of ceramic tiles is achieved. Tactile and striking visual effects.

CN119330592AActive Publication Date: 2025-01-21GUANG DONG QING YUAN MENG NA LI SHA JIAN TAO YOU XIAN GONG SI
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411476789.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-21
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Traditional ceramic tiles lack innovation and artistic sense, and it is difficult to meet the diversified needs of modern decorative design, and the existing granular frit powder is difficult to meet consumers' needs for improving aesthetic pursuits and diversified decorative styles.

Method used

Using specially designed ice needle dry particles, through inkjet printing decorative patterns and applying ice needle dry particle glaze, combined with the application of matte covering glaze, a ceramic tile with an ice needle-like texture visual effect that highly simulates natural ice needles is formed.

Benefits of technology

The glaze of ceramic tiles has excellent texture, good touch and transparency, and meets the needs of modern consumers for personality, artistry and visual effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330592A_ABST
    Figure CN119330592A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of architectural ceramics, and particularly relates to an ice needle dry particle, a ceramic tile with an ice needle effect and a preparation method of the ceramic tile. The dry ice needle granules comprise the following mineral components in parts by weight: 20-35 parts of albite, 6-12 parts of kaolin, 8-12 parts of cordierite, 15-25 parts of wollastonite, 10-15 parts of dolomite, 10-18 parts of quartz, 8-15 parts of zircon powder and 1-5 parts of zinc oxide. According to the invention, by using the specially designed ice needle dry particles, the obtained ceramic tile glaze surface has a visual effect of highly simulating the ice needle-shaped texture of the natural ice needle, and the glaze surface has excellent texture and good touch and transparency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building ceramics, and in particular relates to ice needle dry particles, ceramic tiles with ice needle effects and a preparation method thereof. Background Art

[0002] With the rapid development of the building ceramics industry, ceramic tiles are widely used in the field of building decoration materials due to their unique texture and physical properties. However, traditional ceramic tiles lack innovation and artistry, and are difficult to meet the diversified needs of modern decoration design. In recent years, young consumer groups have emerged, their aesthetic level has continued to improve, and their requirements for building decoration materials have also increased. At present, young consumers are more inclined to choose ceramic tile products that can show their personality, are artistic, and have novel visual effects.

[0003] At present, granular frit powder is widely used in the market as the main material to enhance the surface texture of ceramic tiles, aiming to more accurately imitate the natural texture and touch of natural stone. Its particle size range is usually controlled between 100 and 250 meshes to achieve an ideal balance between visual effects and physical properties. However, with the increasing pursuit of aesthetics by consumers and the diversification of decorative styles, traditional granular frit powder can no longer meet all market demands. In order to promote the development of the ceramic industry to a higher level, the industry has begun to actively explore frit powder materials with different forms (such as flakes, needles, flocs, strips, etc.).

[0004] Chinese patent CN 114014698 A discloses a flaky silver-luster ceramic rock plate and a preparation method thereof, wherein high-refractive-index zirconium oxide with a specific phase composition is prepared into a zirconium sheet and spread on the surface of the brick, and the refractive index difference between the zirconium sheet and the glass phase formed after the transparent glaze is fired is used to make the glaze surface of the zirconium sheet decorative part have a reflective effect.

[0005] Chinese patent CN 118388138 B discloses a needle-shaped crystal particle and its application, which is formed by melting the raw material under high temperature conditions to form a liquid, then cooling and crystallizing, and then rapidly cooling and disintegrating into incomplete small crystals, and various forms of needle-shaped effect textures will naturally form in the crystals. Summary of the invention

[0006] In view of the above problems, the object of the present invention is to provide an ice needle dry particle, a ceramic tile with an ice needle effect and a preparation method thereof. By using specially designed ice needle dry particles, the ceramic tile glaze obtained by the present invention has an ice needle-like texture visual effect that highly simulates the ice needles in nature, and the glaze has excellent texture and good touch and transparency.

[0007] In a first aspect, the present invention provides a dry ice needle granule. The mineral composition of the dry ice needle granule includes, by weight, 20 to 35 parts of albite, 6 to 12 parts of kaolin, 8 to 12 parts of cordierite, 15 to 25 parts of wollastonite, 10 to 15 parts of dolomite, 10 to 18 parts of quartz, 8 to 15 parts of zircon powder, and 1 to 5 parts of zinc oxide.

[0008] Preferably, the chemical composition of the ice needle dry particles includes: SiO 2 :55%~59%;Al 2 O 3 :17%~19%;Fe 2 O 3 :0.1%~0.3%; TiO 2 :0.1%~0.3%; CaO: 7%~10%; MgO: 0.8%~1.2%; K 2 O: 0.7%~1.3%; Na 2 O: 4% to 4.8%; ZrO 2 : 6.4% ~ 9%; ZnO: 1.9% ~ 4.9%.

[0009] Preferably, the mesh size of the ice needle dry particles is 30 to 40 meshes.

[0010] Preferably, the visible light transmittance of the ice needle dry particles after firing is 15% to 20%.

[0011] In a second aspect, the present invention provides a method for preparing a ceramic tile having an ice needle effect. The preparation method comprises the following steps: Applying base glaze on the surface of the body; Inkjet printing a decorative pattern on the surface of the blank after applying the base glaze; Applying ice needle dry particle glaze containing the ice needle dry particles on the surface of the blank after the inkjet printing of the decorative pattern; Apply matte covering glaze on the surface of the body after applying ice needle dry granular glaze; The green body, which has been covered with a matte glaze, is fired to obtain a ceramic tile with an ice needle effect.

[0012] Preferably, the ice needle dry particle glaze is applied by pouring glaze; preferably, the specific gravity of the ice needle dry particle glaze is 1.18±0.1g / cm 3 , glaze application amount is 160~220g / m 2 .

[0013] Preferably, the mineral composition of the matte covering glaze includes: in parts by weight, 10-20 parts of matte frit, 10-15 parts of potassium feldspar, 25-35 parts of sodium feldspar, 10-18 parts of dolomite, 6-12 parts of washed ball clay, 5-10 parts of calcined kaolin, 5-10 parts of strontium carbonate, 4-10 parts of wollastonite, 1-6 parts of aluminum oxide, and 1-6 parts of zinc oxide.

[0014] Preferably, the chemical composition of the matte frit includes: SiO 2 :51%~54%;Al 2 O 3 :17%~19%;Fe 2 O 3 :0.1%~0.2%; TiO 2 :0.2%~0.5%; CaO: 7.2%~9%; MgO: 2.5%~3.2%; K 2 O: 2.6%~3.6%; Na 2 O: 3.8% to 4.6%; BaO: 4% to 4.9%; SrO: 3.6% to 5%.

[0015] Preferably, the mineral composition of the matte frit includes, by weight, 5-15 parts of kaolin, 20-30 parts of potassium feldspar, 15-25 parts of sodium feldspar, 5-15 parts of limestone, 5-11 parts of barium carbonate, 3-8 parts of aluminum oxide, 5-12 parts of talc, and 4-7 parts of strontium carbonate.

[0016] Preferably, the chemical composition of the matte covering glaze includes: SiO 2 :44%~49%;Al 2 O 3 :14%~17%;Fe 2 O 3 :0.1%~0.2%; TiO 2 :0.2%~0.5%; CaO: 6.5%~7.3%; MgO: 1.7%~2.1%; K 2 O: 1.9%~2.7%; Na 2 O: 3.6% to 4.3%; ZnO: 1% to 5.6%; BaO: 1.2% to 1.9%; SrO: 4% to 4.6%; loss on ignition: 9% to 12%.

[0017] Preferably, the matte covering glaze is applied by pouring glaze; preferably, the specific gravity of the matte covering glaze is 1.89±0.1g / cm 3 , glaze application amount is 400~450g / m 2 .

[0018] Preferably, the chemical composition of the base glaze includes: SiO 2 :56%~60%;Al 2 O 3 :26%~29%;Fe 2 O 3 :0.1%~0.3%; TiO 2 :0.2%~0.5%; CaO: 0.5%~0.8%; MgO: 0.1%~0.3%; K 2 O: 3.5%~4.7%; Na 2 O: 3.2%~4.3%; ZrO 2 : 4%~4.9%; loss on ignition: 1%~3%.

[0019] Preferably, the mineral composition of the base glaze includes, by weight, 30-45 parts of potassium feldspar, 5-12 parts of sodium feldspar, 18-28 parts of nepheline, 6-12 parts of kaolin, 10-16 parts of ultra-white alumina, 5-12 parts of quartz, and 6-8 parts of zirconium silicate.

[0020] Preferably, the base glaze is applied by pouring glaze; preferably, the specific gravity of the base glaze is 1.89±0.1g / cm 3 , glaze application amount is 480~520g / m 2 .

[0021] Preferably, the maximum firing temperature is 1198-1205° C., and the firing period is 45-55 minutes.

[0022] In a third aspect, the present invention provides a ceramic tile with an ice needle effect. The ceramic tile with an ice needle effect is obtained according to the preparation method.

[0023] Beneficial Effects

[0024] The present invention uses specially designed ice needle dry particles, so that the obtained ceramic tile glaze has an ice needle-like texture visual effect that highly simulates ice needles in nature, and the glaze has excellent texture and good touch and transparency. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a brick surface effect diagram of the ice needle effect ceramic brick prepared in Example 1; Figure 2 This is a brick surface effect diagram of the ice needle effect ceramic brick prepared in Example 2; Figure 3 This is a brick surface effect diagram of the ceramic brick prepared in Comparative Example 1. DETAILED DESCRIPTION

[0026] The present invention is further described below by the following embodiments in combination with the accompanying drawings. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention. The following is an exemplary description of the preparation method of the ceramic tile with ice needle effect of the present invention.

[0027] The green body is prepared by pressing and molding the green body powder. The chemical composition of the green body powder is not limited, and the green body powder commonly used in the art can be used. The green body raw material is ball-milled and powder-sprayed to obtain the green body powder.

[0028] The molding method includes but is not limited to dry pressing. The green body powder is conveyed into a press mold and pressed to obtain a ceramic green body. For example, a brick green body is obtained by pressing at a pressure of 320 bar. The size of the green body can be changed as required. A green body of 800 mm × 800 mm can be used.

[0029] The green body is dried. It can be dried in a drying kiln. The drying temperature can be adjusted as needed. For example, the drying cycle is 55 minutes. The moisture content of the dried green body is preferably controlled within 0.2wt% to 0.5wt%.

[0030] The base glaze is applied on the surface of the brick. The base glaze is used to cover the defects of the brick and to assist the inkjet printing ink in developing color. For example, the chemical composition of the base glaze includes: SiO 2 :56%~60%;Al 2 O 3 :26%~29%;Fe 2 O 3 :0.1%~0.3%; TiO 2 :0.2%~0.5%; CaO: 0.5%~0.8%; MgO: 0.1%~0.3%; K 2 O: 3.5%~4.7%; Na 2 O: 3.2%~4.3%; ZrO 2 : 4%~4.9%; loss on ignition: 1%~3%.

[0031] In some embodiments, the mineral composition of the base glaze includes, by weight, 30 to 45 parts of potassium feldspar, 5 to 12 parts of sodium feldspar, 18 to 28 parts of nepheline, 6 to 12 parts of kaolin, 10 to 16 parts of ultra-white alumina, 5 to 12 parts of quartz, and 6 to 8 parts of zirconium silicate.

[0032] According to the mineral composition of the base glaze, the raw materials (counted as dry materials) are weighed, and water and additives are added for ball milling. The mass ratio of dry materials to water can be 100: (10-60). For example, the mass ratio of dry materials to water can be 100: 40. Additives include but are not limited to sodium carboxymethyl cellulose and sodium tripolyphosphate. Among them, sodium carboxymethyl cellulose can account for 0.1wt% to 0.4wt% of the mineral composition of the base glaze, and sodium tripolyphosphate can account for 0.1wt% to 0.4wt% of the mineral composition of the base glaze. For example, sodium carboxymethyl cellulose can account for 0.15wt% of the mineral composition of the base glaze, and sodium tripolyphosphate can account for 0.35wt% of the mineral composition of the base glaze. The ball-milled slurry is subjected to iron removal, sieving, aging, and homogenization to obtain a base glaze slurry. The base glaze slurry can have a sieve residue of 0.6±0.1wt% after passing through a 325-mesh sieve. In some embodiments, the viscosity of the base glaze slurry is 220±20Pa·s. When using the base glaze, water can be added to the base glaze slurry to adjust the final required glaze slurry specific gravity. The flow rate of the base glaze slurry on the brick surface can be 27s / 50ml.

[0033] The base glaze may be applied by a glazing process. In some embodiments, the base glaze has a specific gravity of 1.89±0.1 g / cm 3 , glaze application amount is 480~520g / m 2 If the amount of base glaze applied is too little, it will be difficult to cover the color of the body, which will weaken the color development ability of the ink; if the amount of base glaze applied is too much, it will increase the production cost and be unfavorable for the exhaust of the body, which will lead to more pores on the brick surface.

[0034] In some embodiments, the thermal expansion coefficient of the base glaze at 600°C is 8.8×10 -6 / K~9.0×10 -6 / K. For example, the thermal expansion coefficient of the base glaze at 600°C is 8.9012×10 -6 / K.

[0035] The decorative pattern is printed by inkjet on the surface of the blank after the base glaze is applied. The inkjet printing pattern can be selected according to the layout design. The texture and color of the inkjet printed pattern can be adaptively changed according to the layout design.

[0036] Ice needle dry particle glaze containing ice needle dry particles is applied on the surface of the body after the inkjet printing of the decorative pattern. The function of the ice needle dry particles is to enhance the decorative texture of the ceramic tile surface and improve the product grade.

[0037] In some embodiments, the mineral composition of the ice needle dry particles includes, by weight, 20 to 35 parts of albite, 6 to 12 parts of kaolin, 8 to 12 parts of cordierite, 15 to 25 parts of wollastonite, 10 to 15 parts of dolomite, 10 to 18 parts of quartz, 8 to 15 parts of zircon powder, and 1 to 5 parts of zinc oxide.

[0038] Sodium feldspar can accelerate the melting rate of minerals such as quartz, zircon powder, and clay; wollastonite, dolomite, and zinc oxide provide divalent oxide fluxes such as calcium oxide, magnesium oxide, and zinc oxide, forming a composite flux with the monovalent oxide flux. At high temperatures, these fluxes not only promote the chemical reactions between the raw materials, but also help to form a more complex and ordered crystal structure. These structures are interwoven with crystals of various forms and types, which brings unique physical and chemical properties to the ice needle dry particles; cordierite will be converted into a large amount of α-cordierite crystal phase during the high-temperature sintering process. The excellent thermal stability and extremely low thermal expansion coefficient of this crystal phase can effectively prevent material deformation or cracking caused by temperature changes, thereby improving the thermal stability of the ice needle dry particles. Zircon powder has a special tetragonal crystal structure. Although it may retain its original tetragonal crystal phase after high-temperature sintering, some zircon elements react with other minerals to form new compounds or crystal phases. They can not only affect the crystal structure and microscopic morphology of ice needle dry particles, but also have a positive impact on the presentation of ice needle effect by changing the scattering and reflection mode of light. On the other hand, zircon powder is a key opacifier material in ice needle dry particles. The crystal phase formed during the sintering process is often in an opaque state. This opaque state can effectively scatter light, causing light to be diffusely reflected when passing through ice needle dry particles, thereby reducing the transmittance of visible light. By accurately controlling the addition ratio of zircon powder or adjusting its crystallization degree, the visible light transmittance of ice needle dry particles can be flexibly adjusted. Zinc oxide can further improve the opacifying effect of ice needle dry particles and promote crystallization. Zinc oxide reacts with aluminum to form zinc-aluminum spinel. This crystal phase also has excellent scattering properties and can further enhance the scattering effect of light inside ice needle dry particles. Wollastonite, dolomite and quartz can also adjust the glossiness and hardness. The physical composition of the calcined ice needle dry particles includes potassium-sodium feldspar crystal phase, calcium feldspar crystal phase, zircon crystal phase and zinc-aluminum spinel crystal phase.

[0039] The ice needle dry particles are prepared according to the following steps: the mineral raw materials of the ice needle dry particles are mixed in proportion, placed in a crucible, a pool furnace, and a rotary furnace, and smelted at a high temperature of 1450 to 1600°C to obtain glass liquid, and then the molten glass liquid is poured into cold water for quenching to form a crisp block, and then dried to obtain a frit. The obtained block frit can be crushed and sieved to obtain ice needle dry particles of the desired particle size. The mesh number of the ice needle dry particles can be 30 to 40 meshes. The shape of the ice needle dry particles can be flaky. For example, after the block frit is dried, it is transferred to a machine for flaking to obtain flaky ice needle dry particles. In some embodiments, the thickness of the ice needle dry particles is 0.2 to 0.5 mm; the diagonal length is 2 to 6 mm. The visible light transmittance of the ice needle dry particles after sintering is 15% to 20%.

[0040] In some embodiments, the thermal expansion coefficient of the ice needle dry particles at 600°C is 4.1×10 -6 / K~4.3×10-6 / K. For example, the thermal expansion coefficient of the ice needle dry particles at 600°C is 4.236×10 -6 / K.

[0041] Prepare ice needle dry particle glaze slurry. The ice needle dry particle glaze slurry is prepared from ice needle dry particles and a suspending agent. The suspending agent can be mixed with sodium methyl cellulose, ethylene glycol, bentonite, and water. Bentonite can improve the suspending property and adhesion ability of the suspending agent. According to the raw material composition of the suspending agent, the materials are weighed and stirred evenly to prepare the suspending agent. In some technical schemes, the mass ratio of sodium methyl cellulose: ethylene glycol: bentonite: water is 1-5:40-60:2-8:40-50. For example, the mass ratio of sodium methyl cellulose: ethylene glycol: bentonite: water is 3:50:5:42. The amount of ice needle dry particles and the suspending agent can be adjusted as needed. For example, the mass ratio of the suspending agent: ice needle dry particles can be 100-120:5-10.

[0042] In some technical solutions, the chemical composition of the ice needle dry particles includes: SiO 2 :55%~59%;Al 2 O 3 :17%~19%;Fe 2 O 3 :0.1%~0.3%; TiO 2 :0.1%~0.3%; CaO: 7%~10%; MgO: 0.8%~1.2%; K 2 O: 0.7%~1.3%; Na 2 O: 4% to 4.8%; ZrO 2 : 6.4% ~ 9%; ZnO: 1.9% ~ 4.9%.

[0043] The ice needle dry granular glaze can be applied by a glazing process. In some embodiments, the specific gravity of the ice needle dry granular glaze is 1.18±0.1 g / cm 3 , glaze amount 160~220g / m 2 .

[0044] Matte covering glaze is applied on the surface of the body after applying ice needle dry granular glaze. Matte covering glaze can give the surface of ceramic tiles a soft and delicate touch, while also resisting wear and tear in daily use and extending the service life of ceramic tiles.

[0045] In some embodiments, the mineral composition of the matte covering glaze includes, by weight, 10 to 20 parts of matte frit, 10 to 15 parts of potassium feldspar, 25 to 35 parts of sodium feldspar, 10 to 18 parts of dolomite, 6 to 12 parts of washed ball clay, 5 to 10 parts of calcined kaolin, 5 to 10 parts of strontium carbonate, 4 to 10 parts of wollastonite, 1 to 6 parts of aluminum oxide, and 1 to 6 parts of zinc oxide.

[0046] In some technical solutions, the chemical composition of the matte frit includes: SiO 2 :51%~54%;Al 2 O 3 :17%~19%;Fe 2 O 3 :0.1%~0.2%; TiO 2 :0.2%~0.5%; CaO: 7.2%~9%; MgO: 2.5%~3.2%; K 2 O: 2.6%~3.6%; Na 2 O: 3.8% to 4.6%; BaO: 4% to 4.9%; SrO: 3.6% to 5%.

[0047] In some embodiments, the mineral composition of the matte frit includes: by weight, 5-15 parts of kaolin, 20-30 parts of potassium feldspar, 15-25 parts of sodium feldspar, 5-15 parts of limestone, 5-11 parts of barium carbonate, 3-8 parts of aluminum oxide, 5-12 parts of talc, and 4-7 parts of strontium carbonate. By pre-forming the raw material into frit, the stability of the glaze can be improved and the generation of defects can be reduced.

[0048] After weighing the matte frit according to its mineral composition, it is melted at a high temperature of 1400°C to 1500°C (e.g. 1450°C) in a frit furnace to obtain molten glass; the molten glass is poured into cold water for quenching, and the molten glass forms a frit when it is cooled, which is then crushed and sieved to obtain dry granular powder. The mesh number of the matte frit can be 150 to 200 meshes.

[0049] In some technical solutions, the chemical composition of the matte covering glaze includes: in mass percentage, SiO 2 :44%~49%;Al 2 O 3 :14%~17%;Fe 2 O 3 :0.1%~0.2%; TiO 2 :0.2%~0.5%; CaO: 6.5%~7.3%; MgO: 1.7%~2.1%; K 2 O: 1.9%~2.7%; Na 2 O: 3.6% to 4.3%; ZnO: 1% to 5.6%; BaO: 1.2% to 1.9%; SrO: 4% to 4.6%; loss on ignition: 9% to 12%.

[0050] According to the mineral composition of the matte covering glaze, the raw materials (counted as dry materials) are weighed, and water and additives are added for ball milling. The mass ratio of dry materials to water can be 100:10-60. For example, the mass ratio of dry materials to water can be 100:40. Additives include but are not limited to sodium carboxymethyl cellulose and sodium tripolyphosphate. Among them, sodium carboxymethyl cellulose can account for 0.1wt%-0.4wt% of the mineral composition of the matte covering glaze, and sodium tripolyphosphate can account for 0.1wt%-0.4wt% of the mineral composition of the matte covering glaze. For example, sodium carboxymethyl cellulose can account for 0.15wt% of the mineral composition of the matte covering glaze, and sodium tripolyphosphate can account for 0.3wt% of the mineral composition of the matte covering glaze. The ball-milled slurry is subjected to iron removal, sieving, aging, and homogenization to obtain a matte covering glaze slurry. The matte covering glaze slurry can have a sieve residue of 0.4±0.1wt% after passing through a 325-mesh sieve. When using the matte covering glaze, water can be added to the matte covering glaze slurry to adjust the final desired glaze slurry specific gravity. The flow rate of the matte covering glaze on the surface of the brick can be 28s / 50ml.

[0051] The matte covering glaze can be applied by a glazing process. In some embodiments, the specific gravity of the matte covering glaze is 1.89±0.1 g / cm 3 , glaze application amount is 400~450g / m 2 The amount of matte covering glaze applied is too much, the color rendering ability of the design pattern becomes poor, and the glaze surface becomes opaque.

[0052] In some embodiments, the thermal expansion coefficient of the matte covering glaze at 600°C is 7.9×10 -6 / K~8.1×10 -6 / K. For example, the thermal expansion coefficient of the matte covering glaze at 600°C is 8.0111×10 -6 / K.

[0053] The green body after applying matte glaze is fired. It can be fired in a kiln. For example, the highest firing temperature is 1198-1205°C, and the firing cycle is 45-55 minutes. Under this firing system, the ice needle dry particles have good chemical stability and stable emulsification effect, avoiding adverse physical and chemical changes.

[0054] In summary, the present invention uses ice needle dry particles with low expansion coefficient, good thermal stability and visible light transmittance of 15% to 20% after firing. During the high-temperature firing process, the ice needle dry particles will not produce adverse physical and chemical reactions with the matte covering glaze, and have a texture, texture and visual effect that highly simulates the ice needles in nature. Moreover, under the covering effect of the matte covering glaze, the ice needle dry particles still retain their characteristics and the glaze surface has good touch and transparency.

[0055] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation on the present invention.

[0056] Example 1

[0057] In this embodiment, a ceramic tile with an ice needle effect is prepared according to the following steps:

[0058] S1. Pressing the green body.

[0059] S2. Applying a base glaze on the body. The mineral composition of the base glaze includes: by weight, 34 parts of potassium feldspar, 5 parts of sodium feldspar, 23 parts of nepheline, 10 parts of kaolin, 14 parts of ultra-white alumina, 7 parts of quartz, and 7 parts of zirconium silicate. The chemical composition of the base glaze includes: by mass percentage, SiO 2 :57.45%;Al 2 O 3 :27.48%;Fe 2 O 3 :0.21%;TiO 2 :0.26%; CaO: 0.54%; MgO: 0.15%; K 2 O: 3.88%; Na 2 O: 3.71%; ZrO 2 : 4.42%; loss on burning: 1.9%. The base glaze is applied by pouring glaze process. The specific gravity of the base glaze is 1.89g / cm 3 , glaze application amount is 500g / m 2 .

[0060] S3, inkjet printing a decorative pattern on the base glaze-applied body.

[0061] S4. Apply ice needle dry particle glaze on the blank after the decorative pattern is inkjet printed. The mineral composition of the ice needle dry particles includes: in parts by weight, 28 parts of albite, 7 parts of kaolin, 9 parts of cordierite, 18 parts of wollastonite, 10 parts of dolomite, 13 parts of quartz, 12 parts of zircon powder, and 3 parts of zinc oxide. The materials are weighed and mixed according to the proportion of the mineral raw materials of the ice needle dry particles, placed in a crucible, and smelted at a high temperature of 1450°C to obtain molten glass. The molten glass is poured into cold water in a molten state for quenching, and it is made into a crisp block by rapid cooling. The block melt is dried and conveyed to a machine for flaking to obtain ice needle dry particles. The chemical composition of the ice needle dry particles includes: in mass percentage, SiO 2 :56.81%;Al 2 O 3 :17.88%;Fe 2 O 3 :0.14%;TiO 2 :0.16%; CaO: 8.46%; MgO: 0.84%; K 2 O: 0.89%; Na 2 O: 4.37%; ZrO 2 :7.56%;ZnO:2.89%。After firing, the transmittance of the ice needle dry particles to visible light was 16% as detected by instruments。Prepare the suspension agent by weighing and stirring the materials in a mass ratio of sodium methylcellulose: ethylene glycol: bentonite: water = 3:50:5:42。Prepare the ice needle dry particles glaze by weighing and stirring the materials in a mass ratio of suspending agent: ice needle dry particles = 100:6。Prepare the ice needle dry particles glaze by pouring glaze process。The specific gravity of the ice needle dry particles glaze is 1.18g / cm 3 , glaze application amount is 200g / m 2 .

[0062] S5. Apply matte covering glaze on the body after applying ice needle dry granular glaze. The mineral composition of the matte covering glaze includes: in parts by weight, 12 parts of matte frit, 11 parts of potassium feldspar, 28 parts of sodium feldspar, 14 parts of dolomite, 11 parts of washed ball clay, 6 parts of calcined kaolin, 6 parts of strontium carbonate, 8 parts of wollastonite, 2 parts of aluminum oxide, and 2 parts of zinc oxide. Among them, the mineral composition of the matte frit includes: in parts by weight, 12 parts of kaolin, 26 parts of potassium feldspar, 22 parts of sodium feldspar, 14 parts of limestone, 9 parts of barium carbonate, 4 parts of aluminum oxide, 8 parts of talc, and 5 parts of strontium carbonate. The chemical composition of the matte covering glaze includes: in mass percentage, SiO 2 :48.53%;Al 2 O 3 :15.92%;Fe 2 O 3 :0.13%;TiO 2 :0.29%; CaO: 6.95%; MgO: 1.91%; K2 O: 2.44%; Na 2 O: 4.11%; ZnO: 1.97%; BaO: 1.46%; SrO: 4.51%; Loss on ignition: 11.78%. The matte covering glaze is applied by pouring glaze process. The specific gravity of the matte covering glaze is 1.89g / cm 3 , glaze application amount is 420g / m 2 .

[0063] S6. The matte glaze-coated green body is transferred to a kiln for high-temperature firing. After edge grinding and sorting, a finished ceramic tile with an ice needle effect is obtained. The highest firing temperature is 1202°C, and the firing cycle is 47 minutes.

[0064] Figure 1 This is a brick surface effect diagram of the ice needle effect ceramic tile prepared in Example 1. It can be seen that the glaze surface of the ceramic tile has a texture, feel and visual effect that highly simulates the ice needles in nature.

[0065] Example 2

[0066] This embodiment refers to the preparation process of Example 1, and the difference from Example 1 is that the mineral composition of the ice needle dry particles includes: by weight, 28 parts of albite, 7 parts of kaolin, 12 parts of cordierite, 18 parts of wollastonite, 11 parts of dolomite, 13 parts of quartz, 10 parts of zircon powder, and 3 parts of zinc oxide. The chemical composition of the ice needle dry particles includes: by mass percentage, SiO 2 :57.18%;Al 2 O 3 :18.01%;Fe 2 O 3 :0.17%;TiO 2 :0.17%; CaO: 8.58%; MgO: 1.07%; K 2 O: 0.92%; Na 2 O: 4.45%; ZrO 2 :6.53%;ZnO:2.92%. The transmittance of the ice needle dry particles to visible light after sintering is 20% as detected by an instrument. The mineral raw materials of the ice needle dry particles are weighed and mixed according to the proportion, placed in a crucible, and smelted at a high temperature of 1600°C to obtain glass liquid, and the glass liquid is poured into cold water in a molten state for quenching, and is made into a crisp block by rapid cooling, and the block melt is dried and conveyed to a machine for flaking to obtain ice needle dry particles.

[0067] Figure 2 This is a brick surface effect diagram of the ice needle effect ceramic brick prepared in Example 2. This embodiment also has an ideal ice needle effect.

[0068] Example 3

[0069] This example refers to the preparation process of Example 1, and the difference from Example 1 is that the materials are weighed and stirred evenly according to the mass ratio of suspending agent to ice needle dry particles = 100:10 to obtain ice needle dry particle glaze. The specific gravity of the ice needle dry particle glaze is 1.19g / cm 3 , glaze application amount is 160g / m 2 Moreover, the specific gravity of the matte covering glaze is 1.89 g / cm 3 , glaze application amount is 450g / m 2 .

[0070] The ice needle effect and touch of the tile surface in this embodiment are basically the same as those in Example 1.

[0071] Example 4

[0072] This embodiment refers to the preparation process of Example 1, and the difference from Example 1 is that the mineral composition of the matte covering glaze includes: by weight, 15 parts of matte frit, 11 parts of potassium feldspar, 28 parts of sodium feldspar, 14 parts of dolomite, 11 parts of washed ball clay, 5 parts of calcined kaolin, 6 parts of strontium carbonate, 8 parts of wollastonite, 3 parts of aluminum oxide, and 2 parts of zinc oxide. The chemical composition of the matte covering glaze includes: by mass percentage, SiO 2 :48.37%;Al 2 O 3 :16.19%;Fe 2 O 3 :0.11%;TiO 2 :0.22%; CaO: 7.11%; MgO: 1.96%; K 2 O: 2.37%; Na 2 O: 4.26%; ZnO: 1.94%; BaO: 1.51%; SrO: 4.58%; loss on ignition: 11.38%.

[0073] In this embodiment, the glaze transparency is improved, the ice needle effect is more obvious, and the touch effect of the brick surface is softer and more delicate.

[0074] Comparative Example 1

[0075] This comparative example refers to the preparation process of Example 1, and the difference from Example 1 is that the mineral composition of the ice needle dry particles includes: by weight, 28 parts of albite, 7 parts of kaolin, 9 parts of cordierite, 18 parts of wollastonite, 10 parts of dolomite, 13 parts of quartz, and 3 parts of zinc oxide. The chemical composition of the ice needle dry particles includes: by mass percentage, SiO 2 :61.55%;Al 2 O 3 :18.13%;Fe 2 O 3 :0.17%;TiO2 :0.19%; CaO: 9.35%; MgO: 1.04%; K 2 O: 0.98%; Na 2 O: 4.87%; ZnO: 3.72%.

[0076] Figure 3 The brick surface effect diagram of the ceramic brick prepared in comparative example 1. The mineral composition of the ice needle dry particles in this comparative example does not contain zircon powder, and the prepared dry particles are transparent, and cannot show the ice needle texture when applied to the surface of the brick.

[0077] Comparative Example 2

[0078] This comparative example refers to the raw materials and preparation process of Example 1, and the difference from Example 1 is that the glaze amount of the ice needle dry granular glaze is 300g / m 2 The results showed that the needle-shaped dry particles on the brick surface were densely distributed, affecting the visual effect.

[0079] Comparative Example 3

[0080] This comparative example refers to the preparation process of Example 1, and the difference from Example 1 is that the glaze amount of the matte covering glaze is 600g / m 2 The results showed that the glaze was white, which affected the color of the design pattern.

[0081] Comparative Example 4

[0082] This comparative example refers to the preparation process of Example 1, and the difference from Example 1 is that the mineral composition of the matte covering glaze includes: by weight, 12 parts of matte frit, 11 parts of potassium feldspar, 28 parts of sodium feldspar, 14 parts of dolomite, 11 parts of washed ball clay, 6 parts of calcined kaolin, 6 parts of strontium carbonate, 8 parts of wollastonite, 8 parts of aluminum oxide, and 2 parts of zinc oxide. The chemical composition of the matte covering glaze includes: by mass percentage, SiO 2 :47.42%;Al 2 O 3 :20.61%;Fe 2 O 3 :0.12%;TiO 2 :0.21%; CaO: 6.47%; MgO: 1.73%; K 2 O: 2.22%; Na 2 O: 3.83%; ZnO: 1.79%; BaO: 1.34%; SrO: 4.27%; loss on ignition: 9.99%.

[0083] The results showed that the comparative example increased the content of aluminum oxide, the glaze was raw and whitish, felt rough, the design patterns and ice needle dry particles were covered, and the expected effect was not achieved.

[0084] Comparative Example 5

[0085] This comparative example refers to the preparation process of Example 1, and the difference from Example 1 is that the application of the ice needle dry particle glaze layer in step S4 is omitted, and the ice needle dry particles are directly mixed into the matte covering glaze in step S5. The mass ratio of the ice needle dry particles to the matte covering glaze is 5:100, and the glazing amount of the mixed ice needle dry particles and the matte covering glaze is 420g / m 2 .

[0086] The results show that although the comparative example has the ice needle effect, the brick surface has many defects, such as glaze missing, glaze marks, depressions, etc., and it is difficult to produce stably. This is because the ice needle dry particles are ridge materials with irregular long strips. They are directly added to the covering glaze slurry. Due to the poor combination of the two, the fluidity of the glaze slurry is affected during the glazing process, causing great trouble to the production stability.

[0087] Comparative Example 6

[0088] This comparative example refers to the preparation process of Example 1, and the difference from Example 1 is that the mineral composition of the ice needle dry particles includes: by weight, 28 parts of albite, 7 parts of kaolin, 18 parts of wollastonite, 10 parts of dolomite, 13 parts of quartz, 12 parts of zircon powder, and 3 parts of zinc oxide. The chemical composition of the ice needle dry particles includes: by mass percentage, SiO 2 :57.57%;Al 2 O 3 :16.63%;Fe 2 O 3 :0.11%;TiO 2 :0.17%; CaO: 8.94%; MgO: 0.49%; K 2 O: 0.86%; Na 2 O: 4.37%; ZrO 2 :7.33%; ZnO:3.53%.

[0089] The results showed that the thermal stability of the ice needle dry particles deteriorated. When applied to the glaze layer and fired at high temperature, the ice needle dry particles cracked. At the same time, the glaze layer in this area bulged, and the brick surface effect did not meet production requirements.

[0090] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A dry ice needle granule, characterized in that: The mineral composition of the ice needle dry particles includes, by weight, 20 to 35 parts of albite, 6 to 12 parts of kaolin, 8 to 12 parts of cordierite, 15 to 25 parts of wollastonite, 10 to 15 parts of dolomite, 10 to 18 parts of quartz, 8 to 15 parts of zircon powder, and 1 to 5 parts of zinc oxide.

2. The ice needle dry particles according to claim 1, characterized in that The chemical composition of the ice needle dry particles includes, by mass percentage, SiO2: 55% to 59%; Al2O3: 17% to 19%; Fe2O3: 0.1% to 0.3%; TiO2: 0.1% to 0.3%; CaO: 7% to 10%; MgO: 0.8% to 1.2%; K2O: 0.7% to 1.3%; Na2O: 4% to 4.8%; ZrO2: 6.4% to 9%; and ZnO: 1.9% to 4.9%.

3. The ice needle dry particles according to claim 1 or 2, characterized in that: The mesh number of the ice needle dry particles is 30 to 40 meshes.

4. The ice needle dry particles according to any one of claims 1 to 3, characterized in that The visible light transmittance of the ice needle dry particles after burning is 15% to 20%.

5. A method for preparing a ceramic tile with an ice needle effect, characterized in that: The preparation method comprises the following steps: Applying base glaze on the surface of the body; Inkjet printing a decorative pattern on the surface of the blank after applying the base glaze; Applying the ice needle dry particle glaze containing the ice needle dry particles according to any one of claims 1 to 4 on the surface of the blank after the inkjet printing of the decorative pattern; Apply matte covering glaze on the surface of the body after applying ice needle dry granular glaze; The green body, which has been covered with a matte glaze, is fired to obtain a ceramic tile with an ice needle effect.

6. The preparation method according to claim 5, characterized in that: The ice needle dry granular glaze is applied by pouring glaze; preferably, the specific gravity of the ice needle dry granular glaze is 1.18±0.1g / cm 3 , glaze application amount is 160~220g / m 2 .

7. The preparation method according to claim 5 or 6, characterized in that: The mineral composition of the matte covering glaze includes, by weight, 10 to 20 parts of matte frit, 10 to 15 parts of potassium feldspar, 25 to 35 parts of sodium feldspar, 10 to 18 parts of dolomite, 6 to 12 parts of washed ball clay, 5 to 10 parts of calcined kaolin, 5 to 10 parts of strontium carbonate, 4 to 10 parts of wollastonite, 1 to 6 parts of aluminum oxide, and 1 to 6 parts of zinc oxide.

8. The preparation method according to claim 7, characterized in that: The chemical composition of the matte frit includes, by mass percentage, SiO2: 51% to 54%; Al2O3: 17% to 19%; Fe2O3: 0.1% to 0.2%; TiO2: 0.2% to 0.5%; CaO: 7.2% to 9%; MgO: 2.5% to 3.2%; K2O: 2.6% to 3.6%; Na2O: 3.8% to 4.6%; BaO: 4% to 4.9%; SrO: 3.6% to 5%; Preferably, the mineral composition of the matte frit includes, by weight, 5 to 15 parts of kaolin, 20 to 30 parts of potassium feldspar, 15 to 25 parts of sodium feldspar, 5 to 15 parts of limestone, 5 to 11 parts of barium carbonate, 3 to 8 parts of aluminum oxide, 5 to 12 parts of talc, and 4 to 7 parts of strontium carbonate.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The chemical composition of the matte covering glaze includes, by mass percentage, SiO2: 44% to 49%; Al2O3: 14% to 17%; Fe2O3: 0.1% to 0.2%; TiO2: 0.2% to 0.5%; CaO: 6.5% to 7.3%; MgO: 1.7% to 2.1%; K2O: 1.9% to 2.7%; Na2O: 3.6% to 4.3%; ZnO: 1% to 5.6%; BaO: 1.2% to 1.9%; SrO: 4% to 4.6%; loss on ignition: 9% to 12%.

10. The preparation method according to any one of claims 5 to 9, characterized in that: The matte covering glaze is applied by pouring glaze; preferably, the specific gravity of the matte covering glaze is 1.89±0.1g / cm 3 , glaze application amount is 400~450g / m 2 .

11. The preparation method according to any one of claims 5 to 10, characterized in that: The chemical composition of the base glaze includes, by mass percentage, SiO2: 56% to 60%; Al2O3: 26% to 29%; Fe2O3: 0.1% to 0.3%; TiO2: 0.2% to 0.5%; CaO: 0.5% to 0.8%; MgO: 0.1% to 0.3%; K2O: 3.5% to 4.7%; Na2O: 3.2% to 4.3%; ZrO2: 4% to 4.9%; loss on ignition: 1% to 3%; Preferably, the mineral composition of the base glaze includes, by weight, 30 to 45 parts of potassium feldspar, 5 to 12 parts of sodium feldspar, 18 to 28 parts of nepheline, 6 to 12 parts of kaolin, 10 to 16 parts of ultra-white alumina, 5 to 12 parts of quartz, and 6 to 8 parts of zirconium silicate.

12. The preparation method according to any one of claims 5 to 11, characterized in that: The base glaze is applied by pouring glaze; preferably, the specific gravity of the base glaze is 1.89±0.1g / cm 3 , glaze application amount is 480~520g / m 2 .

13. The preparation method according to any one of claims 5 to 12, characterized in that: The maximum firing temperature is 1198-1205°C, and the firing cycle is 45-55 minutes.

14. A ceramic tile with an ice needle effect, characterized in that: The ceramic tile with ice needle effect is obtained according to the preparation method described in any one of claims 5 to 13.

Citation Information

Patent Citations

  • Flaky silver glossy ceramic rock plate and preparation method thereof

    CN114014698A

  • Needle-shaped crystal particles and application thereof

    CN118388138B

  • High-temperature infrared radiation glaze and preparation method thereof

    CN102391017A

  • Manufacturing process for ice crackle glaze fine ceramic jewelry

    CN105384451A

  • White glaze, boundary-free ceramic tile containing white glaze and production method of boundary-free ceramic tile

    CN108715516A